Comparison of Paricalcitol (I.V) and Alfacalcidol (I.V) in Treatment of Secondary Hyperparathyroidism (SHPT) in Hemodialysis Patients - Mansoor Abbas Qaisar , Zain ul Abideen , Fateh Sher Chattah , Muhammad Nadeem , Zahid Hafeez, Mansoor Abbas Qaisar , Zain ul Abideen , Fateh Sher Chattah , Muhammad Nadeem , Zahid Hafeez (Journal of Rawalpindi Medical College, 2020)
Objective: To compare the efficacy of Alfacalcidol (I.V) and Paricalcitol (I.V) for the treatment of secondary hyperparathyroidism (SHPT) in hemodialysis patients. Material and Methods: An open-label randomized clinical trial was carried out to compare the efficacy of intravenous paricalcitol and alfacalcidol. We recruited 80 patients with end-stage renal disease receiving maintenance hemodialysis in a tertiary care hospital dialysis unit. The participants were randomly divided into two groups. A wash-out period of one week was decided for each patient in whom he/she did not receive any medication for the treatment of hypocalcemia, hyperphosphatemia, or secondary hyperparathyroidism. Afterward, patients received an expanding dosage of alfacalcidol or paricalcitol for a time of about four months, and then after a further washout period of one week, each group received opposite treatment (paricalcitol or alfacalcidol) for a further four months (16 weeks). Results: The analyzed data for the same end-points revealed no difference between the two groups. No significant statistical difference in terms of calcium levels in both groups was noted. The study also found no big difference in the ability of both drugs to treat secondary hyperparathyroidism, while keeping serum phosphate and calcium levels inside the desired range. The study also found no distinction in the frequency of hypercalcemia and hyperphosphatemia as a side effect of Vitamin D analogue’s treatment. Conclusion: The study concludes that alfacalcidol and paricalcitol are equally effective in the treatment of secondary hyperparathyroidism in the dialysis population. Since Paricalcitol is expensive as compared to alfacalcidol, in an economically challenged country like Pakistan, Alfacalcidol can be a better choice when treating SHPT as we did not find any gross difference in the ability of two drugs to restrict SHPT. Keywords: Alfacalcidol, Paricalcitol, Secondary hyperparathyroidism, Hemodialysis